PEDAGOGICAL AND PSYCHOLOGICAL BASIS OF INTERNAL MANAGEMENT OF UNIVERSAL EDUCATIONAL INSTITUTIONS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
This article describes what issues the internal control plan and execution of a general education institution can include, and its pedagogical and psychological foundations.